Preparation and evaluation of superabsorbent hydrogels for Removing Water from Crude fuel and Gasoline - Ahmed, Mohammed Haitham; Al-Assady, Nadia A. Hussein (Iraqi Journal of Science, 2025)
This research aimed to create eco-friendly superabsorbent gels that excel in swelling and absorption capacity, rapid swelling rate, affordability, and durability, with the ultimate goal of effectively removing water from crude oil and gasoline practically and sustainably. Superabsorbent hydrogels are composed of two main components. The first component is linear polyacrylamide, which acts as a polyelectrolyte. The second component includes varying amounts of acrylamide as a monomer with N, Ǹ-Methylene bis-acrylamide as a cross-linking agent and sodium persulfate as an initiator. This composition is developed using the semi-interpenetrating polymers network technique (semi-IPNs). The hydrogel was characterized using FT-IR, SEM, and XRD techniques. The swelling characteristics was examined of each semi-IPN hydrogel by quantifying the swelling ratio (SR). It was found that it varied from 589 to 5432٪ depending on component quantities and environments. The results showed that the semi-IPNs containing 2 g acrylamide (sample C) have a high SR as compared to semi-IPNs containing 1 g (sample A) in distilled water and alkaline media but less SR in the acidic medium. The effects of various salt solutions on swelling behavior and the efficacy of semi-IPNs in removing water from crude fuel and gasoline were discussed. The resulting hydrogel after revision of the synthesis temperature indicated an increased swelling rate within a value of SRs ranging from 2700% to 4524% in the water-crude oil mixture and 2700% to 5644% in the water-gasoline mixture when subsequent tests were carried out.